Stereotypes and mass media - Gil, Gastón Julián (Universidad Centro Latinoamericano de Economía Humana (Universidad CLAEH), 2021)
The media have played a fundamental role in the spread of sports activities and, particularly, in the durability of certain disciplines as massive phenomena of global reach. But in addition to this, not only the mass media, but also the new digital media and social networks constitute key spaces for the crystallization of certain imaginaries and their stereotypes associated with certain practices, in this case sports. This article will analyze the stereotype of the "serious runner" shaped in the weekly television broadcast of a multinational sports network, ESPN Run. Every episode of this half-hour program usually focuses on a particular race and on the biography as a runner of an individual participant in the same event. Such runners are usually presented as exemplary cases of a lifestyle characterized by a dense set of ethical and aesthetic precepts. These exemplary runners are generally amateurs who exalt their firm commitment to the supposedly virtuous act of running, which also operates as a criterion of identity self-ascription.